Automatic and renewable micro-solid-phase extraction based on bead injection lab-on-valve system for determination of tranexamic acid in urine by UHPLC coupled with tandem mass spectrometry - Fernandes, Sara (2021)
An automatic micro-solid-phase extraction (μSPE) method using on-line renewable sorbent beads followed by liquid chromatography–tandem mass spectrometry (LC–MS/MS) was established for the determination of tranexamic acid (TXA) in urine. The μSPE method was based on the bead injection (BI) concept combined with the mesofluidic lab-on-valve (LOV) platform. All steps of the μSPE–BI–LOV were implemented by computer programming, rendering enhanced precision on time and flow events. Several parameters, including the type of sorbent, volume and composition of the conditioning solution, washing solution, and eluent composition, were evaluated to improve the extraction efficiency. The best results were obtained with a hydrophilic–lipophilic balanced mixed-mode sorbent, decorated with sulfonic acid groups (Oasis MCX), and 99% acetonitrile–water (50:50, v/v)–1% ammonium hydroxide as eluent. Chromatographic separation was performed using a BEH amide column coupled to MS/MS detection in positive ionization mode. Good linearity was achieved (R2 > 0.998) for TXA concentrations in urine ranging from 300 to 3000 ng mL−1, with LOD and LOQ of 30 and 65 ng mL−1, respectively. Dilution integrity was observed for dilution factors up to 20,000 times, providing the extension of the upper limit of quantification to 12 mg mL−1. The method was validated according to international guidelines and successfully applied to urine samples collected during scoliosis surgery of pediatric patients treated with TXA.